2013
DOI: 10.5588/pha.13.0037
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of undiagnosed diabetes among tuberculosis patients in peripheral health facilities in Kerala

Abstract: Setting: Two tertiary care hospitals and 12 peripheral health institutions (PHIs) in Trivandrum, Kerala, India. Objective: To determine factors associated with the prevalence of diabetes mellitus (DM) among tuberculosis (TB) patients and examine differences in the proportion of new DM cases among TB patients diagnosed at tertiary care centres and PHIs. Design: A descriptive study: TB patients diagnosed during March-September 2012 were screened for known DM. Those with unknown DM status were tested for random b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
17
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 7 publications
7
17
1
1
Order By: Relevance
“…32,[36][37][38][39] Our study did not find associations with BMI and type of TB. Although older age was associated with an increased chance of DM, the rate in the younger age group was still above that in the general population.…”
Section: Public Health Actioncontrasting
confidence: 59%
“…32,[36][37][38][39] Our study did not find associations with BMI and type of TB. Although older age was associated with an increased chance of DM, the rate in the younger age group was still above that in the general population.…”
Section: Public Health Actioncontrasting
confidence: 59%
“…Despite these limitations, our results are generalizable to other TB populations in India, particularly those with a similar age range. 11,13,14 …”
Section: Discussionmentioning
confidence: 99%
“…9 Data from India indicate a wide range of DM prevalence (6.5–33%) among TB cases; all of these estimates are much higher than for the general population. 914 More recently, a report from South India showed that over 75% of TB cases had dysglycemia, with 54% meeting the criteria for DM. 15 As the diet and genetics of the people and the epidemiology of dysglycemia are likely to vary in different parts of India, region-specific data are needed, particularly for Western India, where data are limited.…”
mentioning
confidence: 99%
“…3 Studies conducted in India have reported that many TB patients had had undiagnosed DM. 16,25 In a recent prospective study in Kiribati, where all TB patients aged 18 years were tested for DM at the time of TB diagnosis, 55% were newly diagnosed with DM and had not known their DM status before attending the TB clinic.…”
Section: Public Health Action Tb and Diabetes In Fiji 162mentioning
confidence: 99%